2019
DOI: 10.1103/physrevresearch.1.033184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron correlations and chemical pressures on superconductivity of β -type organic compounds

Abstract: We investigate low-temperature electronic states of the series of organic conductors β ′′ -(BEDT-TTF)4[(H3O)M(C2O4)3]G, where BEDT-TTF is bis(ethylenedithio)tetrathiafulvalene, and M and G represent trivalent metal ions and guest organic molecules, respectively. Our structural analyses reveal that the replacement of M and G give rise to systematic change in the cell parameters, especially in the b-axis length, which has positive correlation with the superconducting transition temperature Tc. Analyses of temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…Figure 6 shows the resistivity of β″-(BEDT-TTF)4(H3O)Ru(C2O4)3•G, where G = PhBr, PhCl, or PhF. Ru-PhBr for A = Kx(H3O)1-x has previously been studied by Prokhorova et al [29] with a sample-dependent Tc in the range 2.8-6.3 K. Resistivity measurements on our crystals of β″-(BEDT-TTF)4(H3O)Ru(C2O4)3.PhBr gave a Tc of 2.8 K, which was as expected based on the b axis length [31]. Upon reducing the size of G from PhBr to PhCl or PhF, no superconductivity was observed.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Figure 6 shows the resistivity of β″-(BEDT-TTF)4(H3O)Ru(C2O4)3•G, where G = PhBr, PhCl, or PhF. Ru-PhBr for A = Kx(H3O)1-x has previously been studied by Prokhorova et al [29] with a sample-dependent Tc in the range 2.8-6.3 K. Resistivity measurements on our crystals of β″-(BEDT-TTF)4(H3O)Ru(C2O4)3.PhBr gave a Tc of 2.8 K, which was as expected based on the b axis length [31]. Upon reducing the size of G from PhBr to PhCl or PhF, no superconductivity was observed.…”
Section: Resultssupporting
confidence: 82%
“…This salt (M = Al) is isostructural with bromobenzene salts where M = Fe, Ga, Rh, Ru, Mn, Cr. A relationship between the b axis length and superconducting T c has previously been observed in the Day series [31]. The b axis length of these bromobenzene salts at room temperature showed that the M = Fe salt had the longest b axis and also the highest T c of~3.8 K, while M = Al had the shortest b axis and the lowest T c of~2.5 K. We also reported the isostructural M = Co salt (Co-PhBr), which did not show superconductivity.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations